ChemInform Abstract: An Efficient Protocol for the Synthesis of Novel 1, 2, 3‐Triazole Substituted 4H‐Chromene Derivatives. Issue 9 (March 2015) - Sambasiva Rao, P.; Malla Reddy, G.; Kurumurthy, C.; Veeraswamy, B.; Santhosh Kumar, G.; Shanthan Rao, P.; Narsaiah, B.
Abstract The title compounds (IV) (16 examples) are efficiently obtained by one‐pot multicomponent reaction of various 1‐substituted 1, 2, 3‐triazolecarbaldehydes (I), malononitrile and 1, 3‐cyclohexanedione using potassium carbonate as inexpensive catalyst.